The effects of family dynamics to psychological aspects of transexuals at Kuantan Pahang in 2012 - Draman, Samsul; Mohd Rus, Razman; Musa, Ramli; Ibrahim, mohd (2013)
The purpose of this paper is to show the relationship of male transsexuals with their family structure as well as the level of depression, anxiety and stress. This paper will highlight that there are strong influence of their family relationships with their psychosocial problems. The study employs three interview-filled forms which are socio-demographic form, Asian Family Characteristics Scale and Depression Anxiety Stress Scale (DASS 21). Among 40 respondents, 14 of them were depressed (35%), 18 were anxious (45%) and 14 were stressed (35%). For family relationship, 20 of them are having poor total family value (50%). On further analysis, result shows that those who are having poor total family value are 4 times more likely to develop depression and 7 times more likely to develop stress compare to those who are having normal total family value. In conclusion, this study reveals that family values have a significant effect on psychological aspects of the transsexuals. Apart from that, according to Asian Family Characteristic Scale results, it is revealed that poor family value in Relationship and Family Dynamics component have more likely to develop psychological factors problem in 2 of the components (depression, P-value = 0.043, and stress, P-value = 0.043).